Genetic Variability of Shallot Genotypes Induced by Salicylic Acid Under Drought Conditions - Khotimah, Khusnul; Randi, M. Jusuf; Roni, Roni; Azizah, Farsya (Jurnal Ilmu Pertanian, 2026)
Shallots (Allium cepa L. var. aggregatum) are an important horticultural commodity in Indonesia whose production is highly susceptible to drought stress. This study aims to evaluate the effect of salicylic acid (SA) induction on improving morphological traits and yield components traits under drought conditions and to analyze genetic variability in five shallot varieties. The experimental design used was a Completely Randomized Design-Split Plot Design with 3 replications. The main plot treatment was the variety factor (V) and the subplot factor was the salicylic acid concentration factor (S). The V factor consisted of 5 varieties, namely V1 = Bima Brebes, V2 = Bima Juna, V3 = Tajuk, V4 = Nganjuk Bauci and V5 = Superphilip. While the S factor consisted of 2 levels, namely S0 = without SA (control), and S1 = 1 mM salicylic acid. Each treatment combination was planted under drought stress conditions. The parameters observed included Leaf length , Leaf Number/clump/, dry leaf weight, dry root weight, bulbs number, dry bulbs weight. And dry bulbs weight/clump. Data analysis was carried out using ANOVA and continued with Duncan's advanced test at the 5% level to determine differences between treatments, in addition to calculations of genetic and phenotypic variance, genetic diversity coefficients and broad-sense heritability estimates. The results of the study confirmed that salicylic acid can improve morphological traits and yield components in all varieties. The V1 variety (Bima Brebes) resulting from SA induction tends to have the best improvement in both morphology and yield components. The genetic diversity coefficient has a value ranging from 8.32-31.66%, where high values of Genetic Variation Coefficient (GVC) (>20%) are found in the traits of leaf number/clump, dry leaf weight, dry root weight, bulbs number, dry bulbs weight and dry bulbs weight/clump. Traits with high GVC values can possibly be used as selection parameters. In addition, high broad-sense heritability values (>50%) were found for the Leaf Number/clump, bulbs dry weight, and bulbs dry weight/clump, with estimated values of 52.37%, 50.67%, and 60.19%, respectively. The high broad-sense heritability estimates indicate that these three traits are predominantly genetically controlled.